2021
DOI: 10.1186/s13046-021-01979-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic tumor-derived exosomal miR-31-5p promotes lung adenocarcinoma metastasis by negatively regulating SATB2-reversed EMT and activating MEK/ERK signaling

Abstract: Background Exosomes have emerged as critical mediators of intercellular communication. Hypoxia is widely recognized as a key regulator of tumor aggressiveness, and significantly affects exosome release by tumor cells. However, the effects of exosomes derived from hypoxic lung adenocarcinoma (LUAD) cells are poorly understood. Methods Samples of miRNA isolated from hypoxic LUAD cell-derived exosomes (HExo) and normoxic LUAD cell-derived exosomes (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 38 publications
(41 reference statements)
0
33
0
Order By: Relevance
“…Among them, microRNAs have been regarded as indispensible mediators in LUAD. For example, Yu F and colleagues demonstrated that exosomal miR‐31‐5p derived from hypoxic tumor targeted SATB2 and activated MEK/ERK signaling to facilitate tumor metastasis in LUAD, 32 and Zhan J et al demonstrated that miR‐3130‐5p could drive the growth, metastasis, and EMT progress in LUAD through directly mediating NDUFS1. 33 In addition, Liu H et al revealed the carcinogenic role of miR‐301b‐3p in inducing LUAD cell proliferation, migration, and invasion via inhibiting DLC1.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, microRNAs have been regarded as indispensible mediators in LUAD. For example, Yu F and colleagues demonstrated that exosomal miR‐31‐5p derived from hypoxic tumor targeted SATB2 and activated MEK/ERK signaling to facilitate tumor metastasis in LUAD, 32 and Zhan J et al demonstrated that miR‐3130‐5p could drive the growth, metastasis, and EMT progress in LUAD through directly mediating NDUFS1. 33 In addition, Liu H et al revealed the carcinogenic role of miR‐301b‐3p in inducing LUAD cell proliferation, migration, and invasion via inhibiting DLC1.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic microenvironment exists in the vast majority of tumors, including liver cancer ( Ma et al, 2021a ) and IH ( Wu et al, 2021 ). The hypoxic microenvironment promotes the metastasis of tumor cells ( Yu et al, 2021 ), enhances the tolerance of tumor cells to radiotherapy and chemotherapy ( Sun et al, 2021 ), and also changes the gene expression of tumor cells. HIF-1α is an important transcription factor in hypoxic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SATB2 reduces NSCLC invasiveness through modulation of EMT-relevant proteins as well as histone methylation of G9a [ 31 ]. Further, hypoxic tumor-derived exosomal miR-31-5p triggers LUAD metastases through negative modulation of SATB2-reversed EMT as well as activation of the MEK/ERK pathway [ 32 ]. Downregulated HLF facilitates multiple-organ distant metastases of NSCLC via the PPAR/NF- κ b pathway NSCLC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%